Learning to Write Arabic Using the Imla Method - Sufyan (Penerbit Hellow Pustaka, 2025)
Imla' learning is the type of education provided to teach students how to form words or letters correctly based on imla' rules. Imla’ holds a very important position in Arabic language learning. The objectives of learning imla' include: 1) Practicing punctuation, 2) Writing words and sentences and forming them correctly without adding or subtracting, and being able to distinguish between correct and incorrect writing, 3) Cultivating good habits for students such as maintaining clean writing, precision, caution, listening well, being quick and able to follow, and connecting theory with practice, 4) Enhancing the skill of hand and eye coordination, 5) Providing students with imla' rules so they can be used.